“Nippostrongylus brasiliensis in Rattus norvegicus and Rattus rattus in areas of the city of Guayaquil. Ecuador - Sánchez-Amador, Francisco (Revista Universidad de Guayaquil, 2015)
The city of Guayaquil has a health problem because of rodents, due to excess waste and landfills where they live. Because of this a parasitological study was conducted to determine the existence of Nippostrongylusbrasiliensis in different urban areas of the city. In two years (2013-2015), 139 rodents of which 20 belong to the species Rattus rattus and Rattus norvegicus 119 were collected a total of 99 positive rodents to N. brasiliensis. In 5 of the 9 selected sectors of the city. The nematode Nippostrongylusbrasiliensis was the most prevalent parasite in areas: Coop. Norte Madrigal, Sauces 7, Cdla. Naval Norte, El Quinto Guayas and Cdla.Miraflores where most nematode was found. We report for the first time Nippostrongylusbrasiliensis in Rattus spp., in the city of Guayaquil, Guayas Province.